Morphological and phylogenetic analysis of Caligus spp isolated from Lates calcarifer cultured in floating net cages in Malaysia / Muhd Faizul Helmi bin Ahamad Hasmi - Ahamad Hasmi, Muhd Faizul Helmi (2013)
Asian seabass, Lates calcarifer (Bloch 1790) is the most marketable cultured fin fish in Malaysia. To date, cultured seabass is known to be parasitized by two species of Caligus namely, Caligus epidemicus and Caligus punctatus. However, the documentation regarding on their parasitism is still limited. Thus, the attention of this study is to investigate the occurrence of Caligus spp on L. calcarifer cultured in brackish water floating net cage, with the comparison between both monoculture and polyculture practices. The specific aims are to; (1) calculate the abundance of infection, (2) phenotypic characterization using scanning electron microscopy and (3) phylogenetic analysis based on 28S rRNA gene. Caligus epidemicus samples were isolated from all locations, comprises with more than 90% of the total isolates with the abundance as high as 2.236. It was followed by 47 individuals of C. rotundigenitalis (Yü 1933) and one C. chiastos (Lin and Ho 2003) which was isolated from polyculture practices with the abundance unit of 0.144 and 0.003 respectively. C. punctatus sample was nowhere to be found. SEM proved to be a useful identification tool whereby, clear phenotypic characteristic and anatomical body structure of each species precisely visualized. The images allowed the ordinal classification of the isolates to be re-examined. Molecular-based analysis via 28S rRNA region was carried out using; (1) neighbour-joining (NJ); (2) maximum parsimony (MP) and; (3) maximum likelihood (ML). The information gathered from the partial sequences of 28S rRNA gene revealed monophyletic relationships within the family Caligus in NJ and ML. In contrast, the MP analysis revealed C. epidemicus as a discrete monophyletic group within Caligidae. The interrelationships between the Caligidae lineages were supported as Lepeophtheirus forms a sister group relationship with Caligus. This Caligus-Lepeophtheirus group is well distinguished from other siphonostomatoids. Calanoida forms a basal group to the lineages. As a conclusion, C. epidemicus was the only consistent species to be found ii infesting cultured seabass in both culturing systems within a wide range of water salinity. Despite the low numbers of C. rotundigenitalis and C. chiastos infestations, they may produce a serious challenge for L. calcarifer polyculture farming activity due to their capability of changing host particularly at 24 to 28 ppt. The morphology analysis confirmed that the isolated specimens were C. epidemicus, C. rotundigenitalis and C. chiastos. Molecular technique based on partial sequencing of 28S rRNA gene differentiates our isolates from other Copepoda taxa retrieved from GenBankTM.